Sobre verbos eponímicos - Martínez Linares, Antonia (Acta Hispanica, 2011)
This paper analyses the basic meaning underlying eponymic verbs which are derived from a current politician surname by the sujfixation of -igar, and the way of capturing their diverse lectures. I argue that these verbs share with other denominál verbs an underspecified causative meaning and that their interpretation, like the lectures of denominál verbs in general, is modulated by sublexical or encyclopedic information of the predicate arguments and of the base nouns.